2013
DOI: 10.32738/jeppm.201301.0005
|View full text |Cite
|
Sign up to set email alerts
|

Developing A Strategy to Enact Lean

Abstract: This paper explains the strategy employed by a case study company to implement lean across the business, and to reflect on the success of this approach so other companies may consider this learning and how it might be useful to them. The strategy to enact lean in the case study company was based on creating a number of standard tools/ways of working. These tools can be considered to be standardised work for key aspects of the construction process that the company undertakes. The aim of the tools was to ensure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Among them, a good example comes from Bygballe and Swärd (2014 p. 11), which practice perspective reveals the lean journey is an ongoing effort, "being refined and adapted to the context in which it was used, a process which never really finished". As Morrey et al (2011) confirm, lean implementation needs to be based on adaptation theory.…”
Section: A Review On Lean Construction Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, a good example comes from Bygballe and Swärd (2014 p. 11), which practice perspective reveals the lean journey is an ongoing effort, "being refined and adapted to the context in which it was used, a process which never really finished". As Morrey et al (2011) confirm, lean implementation needs to be based on adaptation theory.…”
Section: A Review On Lean Construction Implementationmentioning
confidence: 99%
“…Many academic studies comment on barriers to lean implementation, most of which are related to organisational difficulties to expose the errors and learn from them (Morrey et al 2011;Poshdar et al 2019;Wandahl 2014). After a detailed examination of relevant literature, Demirkesen et al (2019) identified and categorised 27 common implementation barriers into seven groups, as follows; political, economical, technical, workforce, cultural, managerial, and communication barriers.…”
Section: Common Barriers To Lean Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The team will collectively assess the current situation and will be involved in developing the future state map, as they are the process owners and will have to ensure the long term sustainability of the proposed improvements. The theme of employee involvement and empowerment is one that is fundamental to Lean thinking (Nicholas, 2010;Morrey, Pasquire and Dainty, 2013; Van der Merwe, 2011) and this creates a culture where respect for people is created.…”
Section: Lean Based Water and Energy Efficiency Toolmentioning
confidence: 99%
“…The link between PMS and strategy is powerful if achieved, creating alignment between the two components will provide information on whether the strategy is being implemented and encourage behaviours consistent with it (Neely, 1999). Thus, PM do not operate in a vacuum; rather, PM are heavily influenced by the strategic context of an organisation that is inherently dynamic (Bourne et al, 2000;Morrey et al, 2013). Within a given PMS, there are measures that are indeed indispensable.…”
Section: Introductionmentioning
confidence: 99%